Histone H3K9 demethylase JMJ25 epigenetically modulates anthocyanin biosynthesis in poplar. (23rd October 2018) - Fan, Di; Wang, Xianqiang; Tang, Xiaofeng; Ye, Xiao; Ren, Sha; Wang, Denghui; Luo, Keming
Summary: Anthocyanins are involved in several aspects of development and defence in poplar ( Populus spp.). Although, over the past decades, significant progress has been made in uncovering these anthocyanin biosynthetic and regulatory mechanisms, the fundamental understanding of the epigenetic regulation in this pathway is still largely unclear. Here, we isolated a histone H3K9 demethylase gene JMJ25 from Populus and characterized its role in anthocyanin biosynthesis by genetic and biochemical approaches. JMJ25 was induced by continuous dark treatment. Overexpression of JMJ25 led to downregulated expression of anthocyanin biosynthetic genes in transgenic poplar, resulting in a significant reduction in anthocyanin content. ChIP‐qPCR assays showed that JMJ25 could directly associate with MYB182 chromatin and dynamically demethylate at H3K9me2. Furthermore, JMJ25 also affected the DNA methylation levels of MYB182 . By contrast, knockout of JMJ25 by CRISPR/Cas9 resulted in ectopic anthocyanin accumulation under dark condition and increased expression of anthocyanin biosynthetic genes. Our results support a model in which JMJ25 directly affects MYB182 expression by altering the histone methylation status of its chromatin and DNA methylation, resulting in repression of anthocyanin accumulation. This study uncovered an epigenetic mechanism that modulates anthocyanin biosynthesis in poplar. Significance Statement: This study showed that poplar JMJ25 is involved in the regulation of MYB182 by directly altering the histone methylation status of chromatin and DNA methylation, resulting in repression of anthocyanin accumulation. Our findings provide insight into an epigenetic regulatory mechanism that controls anthocyanin biosynthesis in poplar.